Isolation and Identification of Thermotolerent Acetic Acid Bacteria from Waste Fruits - Sahoo, Bikash Kumar; Mishra, Rashmi Ranjan; Behera, Bikash Chandra (Asian Journal of Biological and Life Sciences, 2020)
In the present study, thirteen thermotolerant acetic acid bacteria were isolated from waste pomegranate and apple fruit in Carr agar medium following the dilution plate technique method at 37°C. The bacterial strain capable to change the colour of the medium from green to yellow were considered asAcetobactersp. Most of the bacterial isolate could able to tolerate 3-4% of ethanol concentration, change the colour and pH of the medium and produce acetic acid in the range of 1.1-15.2 g/L. Among thirteen bacterial strains, the bacterial strain PAAB-3 could able to tolerate maximum ethanol (5%) and produce maximum acetic acid (15.2g/L) at 37°C. On the basis of morphological and biochemical characteristics the bacterial isolate, PAAB-3 is tentatively identified asAcetobacter aceti.
Keywords: Overoxidation; Pomegranate; Thermo tolerant Waste fruits; tic acid